2020
DOI: 10.1016/j.enconman.2020.113005
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of a U-tube thermocell under various Fe(CN)63−/4− concentration

Abstract: Yiji (2020) 'Experimental investigation of a U-tube thermocell under various Fe(CN)63/4 concentration.', Energy conversion and management., 217 . p. 113005.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 49 publications
0
7
0
1
Order By: Relevance
“…Several reports have investigated aqueous TECs. [3][4][5][6][7][8][9][10] One of these involves the use of a thermosensitive-crystallization boosted liquid-state thermocell (TC-LTC) system. TECs with a power conversion efficiency of 2-5% 11 have exceeded the level acceptable for practical use by achieving an efficiency of 11%.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have investigated aqueous TECs. [3][4][5][6][7][8][9][10] One of these involves the use of a thermosensitive-crystallization boosted liquid-state thermocell (TC-LTC) system. TECs with a power conversion efficiency of 2-5% 11 have exceeded the level acceptable for practical use by achieving an efficiency of 11%.…”
Section: Introductionmentioning
confidence: 99%
“…Larger spacing results in a smaller temperature gradient within the electrolyte and a larger time constant for thermally induced diffusion. 121 Specifically, laboratory basic research is shown in Fig. 14a–e (ref.…”
Section: Thermocell Configuration and Applicationsmentioning
confidence: 99%
“…Based on the heat of ion transport in the Born model, the initial contribution from one type of ion to the ionic Seebeck coefficient is relatively low, which is expected to be in the range of 0.1 mV K –1 . ,, Great efforts have been devoted to improving the performance of electrochemical thermoelectric devices from the aspect of both electrolyte and electrode. , Optimizing the electrolyte property is a popular approach to promote the ionic Seebeck coefficient. , For instance, the ratio of thermal diffusion to ion diffusion in the polyelectrolyte is proved to be much higher than that of the aqueous system. This leads to a larger thermovoltage and a more stable response in the polyelectrolyte. ,,, It is worth noting that the difference in the dielectric constant (ε water ≫ ε polyelectrolyte ) cannot achieve such an enhancement because heat transfer and ion transport are both more efficient in the aqueous solution. ,, In addition, other methods are also applied in the electrolytes for higher and more stable energy conversion, such as importing fixed arrayed tunnels and adding redox electrolytes (e.g., ferrocyanide/ferricyanide ).…”
Section: Introductionmentioning
confidence: 99%